2020
DOI: 10.1017/dmp.2020.311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Risk Perception of COVID-19 Disease: A Community-Based Participatory Study

Abstract: Background and Objective: How people behave in a crisis depends on their understanding and evaluation of risk and vulnerability. Therefore this study was conducted to investigate the Iranians’ risk perception of Covid-19 disease. Methods: An online survey was applied which collected information on demographic, the five dimensions of risk perception (cognitive, political, social, cultural, and emotional) and Trust in government among the Iranian users of social networks. Data were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 24 publications
1
32
0
7
Order By: Relevance
“…A preliminary analysis shows that people who put inadequate prevention measures in place scored higher in low risk perception. Many studies refer to the important role of risk perception when establishing behaviour which will protect health in a pandemic [36][37][38][39] Specifically, the review by Bish and Michie [40] shows the association between perceived personal and family susceptibility to the development of a disease and the presence of preventive behaviour (hand washing, household hygiene, wearing masks, etc.) and avoidance behaviour (avoiding going to public places, restaurants, shops, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary analysis shows that people who put inadequate prevention measures in place scored higher in low risk perception. Many studies refer to the important role of risk perception when establishing behaviour which will protect health in a pandemic [36][37][38][39] Specifically, the review by Bish and Michie [40] shows the association between perceived personal and family susceptibility to the development of a disease and the presence of preventive behaviour (hand washing, household hygiene, wearing masks, etc.) and avoidance behaviour (avoiding going to public places, restaurants, shops, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, many previous studies have analysed knowledge, risk perception, and protective behaviour regarding COVID-19 during the pandemic. However, in many of these studies, differences according to the education level of respondents are neglected [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. In some studies, educational differences have been reported.…”
Section: State Of Research Regarding Differences By Education Levelmentioning
confidence: 99%
“…Perceived risk is an important driving force for the public to accept the government's epidemic prevention policies and adopt preventive behaviors. Inadequate government preparation and lack of effective supervision will lead to disastrous results [11]. Joel surveyed Twitter users in 12 countries during the epidemic and pointed out that, in crisis situations, social media plays an important role in monitoring public risk perception and guiding public communication [12].…”
Section: Introductionmentioning
confidence: 99%